CROSS- CULTURAL AWARENESS AND INTERCULTURAL COMPETENCE (Ta'limning zamonaviy transformatsiyasi, 2024)
this article explores the significance of cross-cultural awareness and intercultural competence, highlighting their importance in fostering effective communication, collaboration, and understanding across diverse cultures. It delves into the key elements of cross-cultural awareness and intercultural competence, including cultural self-awareness, empathy, communication skills, and adaptability. В данной статье исследуется значение межкультурного осознания и межкультурной компетенции, подчеркивая их важность в содействии эффективной коммуникации, сотрудничества и понимания в разнообразных культурах. Она подробно рассматривает основные элементы межкультурного осознания и межкультурной компетенции, включая культурное самосознание, эмпатию, навыки коммуникации и адаптивность.